Analysis of spike protein variants evolved in a novel in vivo long-term replication model for SARS-CoV-2 - Dongbum Kim; Jinsoo Kim; Minyoung Kim; Heedo Park; Sangkyu Park; Sony Maharjan; Kyeongbin Baek; Bo Min Kang; Suyeon Kim; Man-Seong Park; Younghee Lee; Hyung-Joo Kwon; et al. (Frontiers in Cellular and Infection Microbiology, 2023)
IntroductionThe spectrum of SARS-CoV-2 mutations have increased over time, resulting in the emergence of several variants of concern. Persistent infection is assumed to be involved in the evolution of the variants. Calu-3 human lung cancer cells persistently grow without apoptosis and release low virus titers after infection.MethodsWe established a novel in vivo long-term replication model using xenografts of Calu-3 human lung cancer cells in immunodeficient mice. Virus replication in the tumor was monitored for 30 days and occurrence of mutations in the viral genome was determined by whole-genome deep sequencing. Viral isolates with mutations were selected after plaque forming assays and their properties were determined in cells and in K18-hACE2 mice.ResultsAfter infection with parental SARS-CoV-2, viruses were found in the tumor tissues for up to 30 days and acquired various mutations, predominantly in the spike (S) protein, some of which increased while others fluctuated for 30 days. Three viral isolates with different combination of mutations produced higher virus titers than the parental virus in Calu-3 cells without cytopathic effects. In K18-hACE2 mice, the variants were less lethal than the parental virus. Infection with each variant induced production of cross-reactive antibodies to the receptor binding domain of parental SARS-CoV-2 S protein and provided protective immunity against subsequent challenge with parental virus.DiscussionThese results suggest that most of the SARS-CoV-2 variants acquired mutations promoting host adaptation in the Calu-3 xenograft mice. This model can be used in the future to further study SARS-CoV-2 variants upon long-term replication in vivo.